Muscle Strength Is Protective Against Osteoporosis in an Ethnically Diverse Sample of Adults. Issue 9 (September 2017) - McGrath, Ryan P.; Kraemer, William J.; Vincent, Brenda M.; Hall, Orman T.; Peterson, Mark D.
Abstract : Abstract: McGrath, RP, Kraemer, WJ, Vincent, BM, Hall, OT, and Peterson, MD. Muscle strength is protective against osteoporosis in an ethnically diverse sample of adults. J Strength Cond Res 31(9): 2586–2589, 2017—The odds of developing osteoporosis may be affected by modifiable and nonmodifiable factors such as muscle strength and ethnicity. This study sought to (a) determine whether increased muscle strength was associated with decreased odds of osteoporosis and (b) identify whether the odds of osteoporosis differed by ethnicity. Data from the 2013 to 2014 National Health and Nutrition Examination Survey were analyzed. Muscle strength was measured with a hand-held dynamometer, and dual-energy x-ray absorptiometry was used to assess femoral neck bone mineral density. A T-score of ⩽2.5 was used to define osteoporosis. Separate covariate-adjusted logistic regression models were performed on each sex to determine the association between muscle strength and osteoporosis. Odds ratios (ORs) were also generated to identify if the association between muscle strength and osteoporosis differed by ethnicity using non-Hispanic blacks as the reference group. There were 2, 861 participants included. Muscle strength was shown to be protective against osteoporosis for men (OR: 0.94; 95% confidence interval [CI]: 0.94–0.94) and women (OR: 0.90; CI: 0.90–0.90). Although ORs varied across ethnicities, non-Hispanic Asian men (OR: 6.62; CI: 6.51–6.72) and women (OR: 6.42; CI: 6.37–6.48) were at highest odds of osteoporosis. Increased muscle strength reduced the odds of osteoporosis among both men and women in a nationally representative, ethnically diverse sample of adults. Non-Hispanic Asians had the highest odds of developing osteoporosis. Irrespective of sex or ethnicity, increased muscle strength may help protect against the odds of developing osteoporosis.